Faktor Risiko Kejadian Diare padaAnak di Puskesmas Toapaya, Toapaya Asri, Kabupaten Bintan, Kepulauan Riau - Yola Mia Jayanti; Dyah Suryani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Background: Diarrhea is one of the major causes of morbidity and mortality around the world and develop countries. In 2014, there were 86 cases of diarrhea in Toapaya Asri District and 34 of them were toddlers. Most of the people already have their own latrines, yet there are still toddlers excrete on improper excretion places. There are also some families who are not having their own excretion facilities in their houses. The lack of knowledge toward individual cleanliness such as the mothers and toddlers hard willingness to wash the hands is also related. The objective of this research is to discover the risk factors of diarrhea incidence to toddlers at Toapaya primary health care in Toapaya Asri Village Regency of Bintan Province of Riau Island. Method: This quantitative research used cross sectional study design by 71 respondents of toddler samples. The primary data in this research were obtained by conducting interviews, observations, questionnaires, and check list. Findings: The relation of toddlers’ excretion behavior and the diarrhea incidence are in P-value 0,002; latrines ownership and the diarrhea incidence are in P-value 0,008. Meanwhile, the variable of mothers’ hand-washing habit has no relation toward the diarrhea incidence from its P-value 1,000; and the variable of toddlers’ handwashing habit has no relation toward the diarrhea incidence from its P-value 0,756. Conclusion : This research shows that the excretion behavior of toddlers and the ownership of latrines relate the diarrhea incidence to toddlers. On the other hand, mothers’ and toddlers’ hand-washing habit has no relation toward the diarrhea incidence. Key Words: Diarrhea, Latrines’ Ownership, Cross Sectiona